Between Calls for Action and Narratives of Denial: Climate Change Attention Structures on Twitter - Hendrik Meyer; Amelia Katelin Peach; Lars Guenther; Hadas Emma Kedar; Michael Brüggemann (Media and Communication, 2023)
The threats posed to society by climate change often fail to become priorities for voters and policymakers. Nevertheless, it has been shown that merely paying online attention to climate change can increase the perceived severity of the associated risks and thus encourage climate action. Therefore, we focus on public discourse on Twitter to explore the interplay of “triggers” and discursive features that stimulate attention to climate change. We collected data from 2017 to 2021, identified each year’s top five “peak” events of climate attention, and applied manual content (N = 2,500) and automated network analyses (N = ~17,000,000). The results show that while specific events and actors may not trigger and maintain attention permanently, there are discursive features (types of domains, discourses, users, and networks) that continuously shape attention to climate change. Debates are highly politicized and often call for action, criticize administrations, stress negative future scenarios, and controversially debate over the reality of climate change. Attention thereby is amplified within hybrid discourses which merge different triggers, being dominated by political, cultural, and journalistic media accounts: Political events trigger posts that stress the reality of climate change, whereas tweets on protests and cultural events are amplified if they call for action. However, antagonism and backlashes to such posts are essential features of the peaks investigated. Accordingly, attention is often connected to controversial debates regarding focusing events, polarizing figures (such as Greta Thunberg or Donald Trump), and the formation of counter-public networks. Which content is amplified highly depends on the subnetworks that users are situated in.